Raman spectroscopy study of reduced strontium barium niobate (SBN61) and hints of supergrowth or intergrowth structures. (4th September 2018) - Primrose, Michael Shoji; Toulouse, Jean; Bock, Jonathan; Randall, Clive
Abstract: Reduced strontium barium niobate, Sr x Ba1 − x Nb2 O6 (SBN), is a potential candidate for oxide thermoelectrics. In order to understand the effects of oxygen reduction on the structure and properties of SBN, room temperature Raman spectra of reduced and unreduced crystals with composition x = 0.61 (SBN61) have been measured, fitted, and compared, for incident light polarized successively along the crystallographic a ‐ and c ‐axes. Unexpectedly, the low wavenumber spectra (<200 cm −1 ) of reduced SBN are found to display much better resolved and intense peaks than those of unreduced SBN, suggestive of a more ordered and compact lattice arrangement in reduced SBN. Shape changes of certain peaks and the disappearance or appearance of other peaks (30 cm −1 /1000 cm −1 ) are also observed as a result of reduction. Comparison of the experimental spectra and fits of the unreduced and reduced crystals are suggestive of a redistribution of the remaining oxygen anions, structural rearrangements, and the development of supergrowth or intergrowth structures in reduced SBN. The reduced spectra are found to be very similar to the published spectra of other complex oxides such as the H‐form of niobium oxide, H‐Nb2 O 5, or TiNb2 O7, which are made up of a regular layered arrangement of blocks of corner‐sharing and edge‐sharing oxygen octahedra. These structural changes may play an important role in the enhanced electrical conductivity of reduced SBN perpendicular to the layers. Abstract : The Raman spectra of a ‐ and c ‐ oriented unreduced and reduced crystals of Strontium Barium Niobate (SBN) have been obtained. The raw spectra are compared in order to identify the spectral changes brought about by reduction, respectively, in the a ‐ and c ‐ oriented crystals and identify their characteristics and differences. The spectra are fitted with damped harmonic oscillator models for a more quantitative analysis of the spectra. Tentative conclusions are drawn as to the effects of the reduction treatment on the molecular structure of reduced SBN.